2020
DOI: 10.3390/ijerph17176122
|View full text |Cite
|
Sign up to set email alerts
|

Case Study in a Working Environment Highlighting the Divergence between Sound Level and Workers’ Perception towards Noise

Abstract: Excessive noise levels are a prevalent issue in food processing operations and, although there have been numerous studies on occupational noise, no single study has used a concurrent mixed-methods approach. Employing this study design allows for an understanding of the level of convergence (similarity) between measured noise levels and workers’ attitudes and perceptions towards noise. This, in turn, allows for the identification of potential challenges with respect to the implementation of hearing conservation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the process of working at the factory, often workers are also very little interested in the risks due to high noise levels affecting their health. The exploratory study confirmed that excessive noise (sound levels greater than 85 dBA) was prevalent in the participating facilities; yet nearly 50% of the exposed workers were nonchalant about this occupational hazard, even though they recognized that the environment was loud [13].…”
Section: Air Quality Variables In Furniture Manufacturersmentioning
confidence: 68%
“…In the process of working at the factory, often workers are also very little interested in the risks due to high noise levels affecting their health. The exploratory study confirmed that excessive noise (sound levels greater than 85 dBA) was prevalent in the participating facilities; yet nearly 50% of the exposed workers were nonchalant about this occupational hazard, even though they recognized that the environment was loud [13].…”
Section: Air Quality Variables In Furniture Manufacturersmentioning
confidence: 68%
“…General hazardous effects of noise on health include, though are not limited to, sleep disturbance (Ntlhakana, Nelson, & Khoza-Shangase, 2020), pulmonary diseases, type 2 diabetes, fatigue, distraction (Hon, Tchernikov, Fairclough, & Behar, 2020), cardiovascular problems (Asady et al, 2021;Hon et al, 2020) and hypertension (Li et al, 2019). The noise exposure was also associated in the literature with injury and accident occurrence, as the annoyance effect clouds judgment and endangers action (Hon et al, 2020;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, earthworks, as an example of similar works, uses the same processes and machines, therefore poses the same risks. However, excessive occupational noise is preventable (Hon et al, 2020). Understanding the general processes that contribute to this problem and mitigate its effects, achieved by carefully planning even the simplest operations.…”
Section: Introductionmentioning
confidence: 99%